The Impact of Transformational Leadership and Management Support on Employee Performance through Organizational Commitment in Shipping Companies - Mursidi, Mursidi; Sarjito, Aris (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
Employee performance is a key factor in organizational success, especially in dynamic industries such as shipping. This study aims to analyze the role of organizational commitment as a mediator in the relationship between transformational leadership, managerial support, and employee performance. This research adopts a qualitative approach based on secondary data, reviewing and synthesizing previous studies to gain a more comprehensive understanding of the relationships among the variables under investigation. The results indicate that transformational leadership enhances employee motivation and engagement, while managerial support plays a role in creating a stable and supportive work environment. However, the influence of these two variables on employee performance is mediated by the level of organizational commitment. Employees with high commitment are more motivated to increase productivity and demonstrate greater loyalty to the organization. Therefore, companies should strengthen leadership strategies, management policies, and create a work culture that supports employee commitment.